Identification of Risk Factors and Consequences of Sexual Violence in Children (Association of Public Health Scholars based in Faculty of Public Health, Sriwijaya University, 2020)
An increase in cases of sexual violence against children triggers various health problems in children, both physical, psychological and social. This paper aims to explore the sexual violence on children, risk factors and the impact of sexual violence on children. This study of sexual violence in children refers to various empirical literature studies. Furthermore, the collection of information was analyzed using the problem tree analysis approach to find out the risk factors and their impact on children. Cases of sexual violence in the community are difficult to detect because of the lack of recognition from victims. This is because the offender called pedophile comes from within the family (familial abuse) or can come from outside the family environment (extra-familial abuse) who have established close relationships with children. Sexual violence is generally motivated by the problem of weak protection from parents which is also strengthened by socio-economic problems, low access to reproductive health education and less optimal law enforcement. Therefore, children who have experienced sexual violence find it difficult to avoid physical, biological, psychological and social risks. Children who have experienced sexual violence find it difficult to avoid physical, biological, psychological and social risks. Therefore, it is necessary to increase the capacity of parents in the prevention of sexual violence against children and law enforcement needs to complete the system of early detection and rapid response to the incidence of sexual violence against children.